Exercising of integrated approach for the specialized meat products development - M. A. Aslanova; O. K. Derevitskaya; A. S. Didikin; A. L. Bero; N. E. Soldatova (Теория и практика переработки мяса, 2024)
The principles of the specialized food products development differ from the traditional technologies, which require the integrated approach to their creation, taking into consideration the specified properties, purpose and type of the food product. This article describes the general algorithm for developing the specialized dietary therapeutic and prophylactic nutrition meat products, and demonstrates the implementation of the individual stages of the algorithm on the example of developing the food products for people who suffer from the most socially significant diseases like diabetes and CVD. The algorithm of methodology is a sequence of stages executed during the product development and a description of their content and practical implementation. The modern approaches to creation of healthy food products for people with socially significant diseases, the recommendations of the World Health Organization based on the analysis of scientific literature posted in open sources and publicly available databases were used as the material of the research, as well as the results of our own studies in the field of technologies for dietary therapeutic and prophylactic nutrition meat products. The specialized meat products for therapeutic and prophylactic nutrition, information about their ingredient composition, nutritional value, results of preclinical and clinical trials were used as the objects of the study. The stages of product creation include medical and biological substantiation of the composition, designing of a virtual model of the food product, technology development, evaluation of the safety and efficiency of the resulting product taking into consideration the technological impact, preclinical and clinical evaluation. The study showed the difference in the approaches to the dietary meat products development depending on the purpose —  whether its therapeutic nutrition or prophylactic nutrition. The developed methodology can be used as a tool that provides for scientifically justified development of the specialized meat products and substantiation of their efficiency.